Ancient Egyptian Furniture Volume I: 4000 -- 1300 BC - Killen, Geoffrey (Oxbow Books, 2017)
List of Figures; List of Plates; Acknowledgements; Abbreviations and Sigla; Chapter 1. Furniture Materials; Chapter 2. Tools; Chapter 3. Bedframes; Chapter 4. Stools; Chapter 5. Chairs; Chapter 6. Tables; Chapter 7. Vase Stands; Catalogue of Museum Collections; Bibliography.